INFLUENCE OF CHILD ABUSE ON CLASSROOM BEHAVIOUR AND ACADEMIC PERFORMANCE AMONG PRIMARY AND SECONDARY SCHOOL STUDENTS - Alokan Funmilola Bosede; Olatunji Itunu Comfort (European Scientific Journal, ESJ, 2014)
This study was carried out to examine the relationship between childabuse and children‘s attention span in class; and the relationship betwenchild‘s active involvement in parent‘s business and attitude to classwork. Adescriptive research design of survey type was adopted for the study.Thepopulation for this study comprised all teachers in primary and secondaryschools in both public and private sectors in Ado local government area ofEkiti State, Nigeria. The sample consisted of 200 teachers drawn from 10schools through stratified random sampling. A questionnaire tagged ‗ChildAbuse and Classroom Behaviour Questionnaire (CACBQ) was used tocollect data. Expert judgements were used to ensure face and contentvalidity. Test-retest method was used to determine the reliability and areliability coefficient of 0.72 was obtained. Data collected were analysed byusing Pearson Product Moment Correlation. The result revealed that there isa significant relationship between child abuse and children‘s attention spanin class. The result also showed that there is a significant relationshipbetween child‘s active involvement in parent‘s business and his/her attitudeto classwork. Based on these findings, it was recommended, among others,that the effects of child abuse on children‘s classroom behaviour and lateracademic performance should receive attention in education policy forums;and that parents should always relate to their children with love and affectionand provide for their needs.